2022
DOI: 10.21603/2074-9414-2022-3-2385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Complex Plant Additive on Flour Mixes and Wheat Dough

Abstract: Food additives from non-traditional plant raw materials are a promising source of new fortified bakery products. However, they can affect the protein-starch structure of wheat flour and the rheological profile of the semi-finished bakery products, thus changing the quality of the finished product. The research objective was to study the effect of a novel plant food additive on the moisture, water absorption, and protein-proteinase complex of flour mixes and the rheological properties of wheat dough. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Structure formation is the result of the formation of intermolecular disulfide bonds between gluten proteins, followed by the development of a gluten network that is responsible for binding starch and other flour components. [10].…”
Section: Determination Of Rheological Properties Of Test Semi-finishe...mentioning
confidence: 99%
See 2 more Smart Citations
“…Structure formation is the result of the formation of intermolecular disulfide bonds between gluten proteins, followed by the development of a gluten network that is responsible for binding starch and other flour components. [10].…”
Section: Determination Of Rheological Properties Of Test Semi-finishe...mentioning
confidence: 99%
“…The changes described above occurring in the test can be visualized using farinograms. It is also worth noting that a typical farinogram of wheat flour (figure 1), without adding additional ingredients, has one peak [10,11]. The results of studies of dough semi-finished products on a farinograph are shown in Table 2.…”
Section: Determination Of Rheological Properties Of Test Semi-finishe...mentioning
confidence: 99%
See 1 more Smart Citation